Increasing the competitiveness of vegetable crops to weeds by improving control methods - A. V. Soldatenko; A. M. Menshich; A. Yu. Fedosov; I. I. Irkov; M. I. Ivanova (Овощи России)
Weeds are a major threat in crop production, and controlling them in modern agriculture is critical to preventing crop losses and ensuring food security. Intensive farming practices, climate change and natural disasters affect weed dynamics, requiring a change in management practices. Existing methods are no longer viable due to lack of manpower; chemical control methods are limited by health hazards and the development of herbicide resistance in weeds. This article discusses some potential alternative weed control strategies in modern vegetable production that are feasible and effective. Increasing the competitiveness of vegetable crops through proper planning of agrotechnologies system, preventive, cultural and mechanical methods, development of competitive varieties, allelopathy, biological control and reduction of weed seed production at harvest will be a major aspect in sustainable weed management. Improving tillage regimes has long been considered the main measure of weed control. Control of weed seed production and weed injuriousness have been shown as potential tools to reduce weed seed germination and retention in the soil. The development of allelopathy has led to the emergence of new methods of weed control. The use of the allelopathic potential of crops also deserves mention in modern weed control methods. Thermal weed control is seen as a useful method. The role of bioherbicides as an integral part of sustainable weed management is emphasized. All of these strategies are viable for modern agriculture; however, choosing a specific method and using the right combinations will be the key to success. No strategy is perfect, and therefore an integrated approach can provide the best results. The adoption of such practices can improve the efficiency of farming systems in sustainable agricul- ture. A comprehensive method for protecting vegetable crops from weeds and ways to reduce the potential contamination of fields with seeds and weed seedlings are described. The optimal norms and technological features, conditions for the effective use of modern herbicides on crops and plantings of vegetable crops are given.